Earthworm-mediated synthesis of silver nanoparticles: a potent tool against hepatocellular carcinoma, Plasmodium falciparum parasites and malaria mosquitoes - Jaganathan, Anitha; Murugan, Kadarkarai; Panneerselvam, Chellasamy; Madhiyazhagan, Pari; Dinesh, Devakumar; Vadivalagan, Chithravel; Aziz, Al Thabiani; Chandramohan, Balamurugan; Suresh, Udaiyan; Rajaganesh, Rajapandian; Subramaniam, Jayapal; Nicoletti, Marcello; et al. (Elsevier, 2016)
The development of parasites and pathogens resistant to synthetic drugs highlighted the needing of novel, eco-friendly and effective control approaches. Recently, metal nanoparticles have been proposed as highly effective tools towards cancer cells and Plasmodium parasites. In this study, we synthesized silver nanoparticles (EW–AgNP) using Eudrilus eugeniae earthworms as reducing and stabilizing agents. EW–AgNP showed plasmon resonance reduction in UV–vis spectrophotometry, the functional groups involved in the reduction were studied by FTIR spectroscopy, while particle size and shape was analyzed by FESEM. The effect of EW–AgNP on in vitro HepG2 cell proliferation was measured using MTT assays. Apoptosis assessed by flow cytometry showed diminished endurance of HepG2 cells and cytotoxicity in a dose-dependent manner. EW–AgNP were toxic to Anopheles stephensi larvae and pupae, LC50 were 4.8 ppm (I), 5.8 ppm (II), 6.9 ppm (III), 8.5 ppm (IV), and 15.5 ppm (pupae). The antiplasmodial activity of EW–AgNP was evaluated against CQ-resistant (CQ-r) and CQ-sensitive (CQ-s) strains of Plasmodium falciparum. EW–AgNP IC50 were 49.3 μg/ml (CQ-s) and 55.5 μg/ml (CQ-r), while chloroquine IC50 were 81.5 μg/ml (CQ-s) and 86.5 μg/ml (CQ-r). EW–AgNP showed a valuable antibiotic potential against important pathogenic bacteria and fungi. Concerning non-target effects of EW–AgNP against mosquito natural enemies, the predation efficiency of the mosquitofish Gambusia affinis towards the II and II instar larvae of A. stephensi was 68.50% (II) and 47.00% (III), respectively. In EW–AgNP-contaminated environments, predation was boosted to 89.25% (II) and 70.75% (III), respectively. Overall, this research highlighted the EW–AgNP potential against hepatocellular carcinoma, Plasmodium parasites and mosquito vectors, with little detrimental effects on mosquito natural enemies.